Pengaruh Gaya Hidup Dan Harga Terhadap Keputusan Pembelian Wardah Exclusive Matte Lip Cream Di Perkumpulan Rutin Ibu-Ibu Rt 03 Desa Sumberwono Kabupaten Mojokerto - Cindy Putri Dwi Lestari; Suyono Suyono (Jurnal Kajian Ilmu Manajemen (JKIM), 2022)
The purpose of this study was to determine the lifestyle. The purpose of the partial influence of lifestyle on the purchasing decision of Wardah Exclusive Matte Lip Cream at the routine association of mothers in RT 03 Sumberwono Village Mojokerto Regency, to determine the effect of price partially on the purchasing decision of Wardah Exclusive Matte Lip Cream at routine gatherings. the women of RT 03 Sumberwono Village Mojokerto Regency, knowing the influence of lifestyle and price partially on the purchasing decision of Wardah Exclusive Matte Lip Cream at the routine gathering of women from RT 03 Sumberwono Village Mojokerto Regency. This research is a quantitative research with survey method. The population of this research is the women of RT 03 Sumberwono Village who are consumers or users of Wardah Exclusive Matte Lip Cream products. Because at the gathering in RT 03, Sumberwono Village, there were 104 people known. The sampling technique used non-probability sampling with purposive sampling method in order to obtain a sample of 50 employees. The data analysis technique used is multiple regression. The test results simultaneously (simultaneously) show that lifestyle and price variables have a positive effect on the purchasing decision of Warda Exclusive Matte Lipcream, it can be proven that the results obtained are 4,469. Lifestyle variables have a significant positive effect on purchasing decisions, this is evidenced by the value of tcount = 2,965 t table 1,678. and the correlation coefficient value shows a relationship of 15.68%. The price variable has effect on purchasing decisions, this is evidenced by the value of tcount = -0,058 t table 1,678. and the correlation coefficient value shows a relationship of 0.44%